PF-5 Case Study: The FLUTD (Feline Lower Urinary Tract Diseases) Incidence on Cats in Qithmir Pet Care Jombang Year 2013-2017 - Nur Fitriah; F Rosa; M Hermawanti; Rini Setiyowati (Hemera Zoa, 2018)
Feline Lower Urinary Tract Diseases (FLUTD) is a disorder or disease of the lower urinary tract in cats known daily as the Urinary Tract Infection (UTI) on the lower or upper part of the tract. In daily practice at Qithmir Pet Care, patients are often present with complaints (signalment) from the owner of dysuria(urinating difficulty), stranguria (pain in urinating process), polakiuria (frequent urination in small amounts), haematuria (bloody urine), periuria (urinate carelessly) and frequent licking of the genitals with decreased appetite, lethargy and vomiting, even in some cases patients come with a critical condition, where various complaints lead to the diagnosis of FLUTD. The purpose of this study are recording, write, and storage data to determine the number of case and the pattern or period of the disease. As an effort to fulfill and supply diagnostic tools, medical equipments, medicines and operator or medical capability in handling the FLUTD case.Case Study: The FLUTD (Feline Lower Urinary Tract Diseases) Incidence on Cats inQithmir Pet Care Jombang Year 2013-2017